A(H1N1)pdm09 Influenza Viruses Replicating in Ferret Upper or Lower Respiratory Tract Differed in Onward Transmission Potential by Air. (24th May 2021) - Xie, Chenyi; Su, Wen; Sia, Sin Fun; Choy, Ka-Tim; Morrell, Steven; Zhou, Jie; Peiris, Malik; Bloom, Jesse D; Yen, Hui-Ling
Abstract: Background: A(H1N1)pdm09 influenza viruses replicate efficiently in respiratory epithelia and are transmitted via respiratory droplets and aerosols expelled by infected hosts. The relative onward transmission potential of influenza viruses replicating in the upper and lower respiratory epithelial cells has not been fully defined. Methods: Wild-type and barcoded A(H1N1)pdm09 viruses that differed by 2 synonymous mutations per gene segment were inoculated into ferrets via intranasal and intratracheal routes. Naive recipients were exposed to the exhaled breath of inoculated donors for 8 hours on day 2 postinoculation. Onward transmission potential of wild-type and barcoded genotypes were monitored by next generation sequencing. Results: Transmissible airborne particles were respired from the upper but not the lower respiratory epithelial cells of donor ferrets. There was limited mixing of viral populations replicating in the upper and lower respiratory tissues. Conclusions: The ferret upper respiratory epithelium was mapped as the anatomic site that generated influenza virus-laden particles mediating onward transmission by air. Our results suggest that vaccines and antivirals should aim to reduce viral loads in the upper respiratory tract for prevention of influenza transmission. Abstract : This study compared the relative onward transmission potential of A(H1N1)pdm09 influenza viruses replicating in the upper and lower respiratory epithelia. The ferret upper respiratory epithelium was mapped as the anatomic site that generated virus-laden particles mediating onward transmission by air.